The Effect of Periodontal and Peri-Implanter Health on IL-1β and TNF-α Levels in Gingival Crevicular and Peri-Implanter Sulcus Fluid: a Cross-Sectional Study - Gündoğar, Hasan (2020)
It is stated that peri-implanter diseases have destructive effects similar to periodontal diseases. This study aims to compare IL-1β and TNF-α levels in healthy and diseased areas. Forty non-smokers systemically health individuals (40 implants/40 teeth) (age:38-67) were included in the study. In clinical and radiographic examinations; plaque index (PIn), gingival index (GI), periodontal pocket depth (PPD), clinical attachment level (CAL) and marginal bone loss (MBL) values were recorded. The gingival crevicular fluid (GCF) and peri-implanter sulcus fluids (PISF) of the patients were collected, and IL-1β and TNF-α levels were measured by ELISA in the samples. The collected data were analyzed with the help of SPSS v.22 package program. Sample PPD score showed a statistically significant difference between the diseased and healthy groups and also sample CAL showed statistically significant higher in Periodontitis(P) compared to periodontally heathy(H) and Gingivitis(G) (p>0.05). IL-1beta and TNF-α levels in GCF/PISF; In the P and Peri-implantitis (PI) group, it was found statistically significantly higher than the H, Healthy-Implant (HI), besides P showed higher levels compared to G (p<0.05). Within the limitations of our study, it can be said that IL-1β and TNF-α among inflammatory cytokines in GCF/PISF will increase in periodontal and peri-implanter diseases, it can also be said that this increase in cytokines may indicate that periodontal and peri-implanter diseases have similar immunological structure. Peri-implant mucositis without periodontitis history has similarity to peri-implantitis and periodontitis in terms of IL-1β and TNF-α levels in GCF/PISF.